Implementation of the Al-Bayan Method in Qur’anic Learning and Its Impact on Early Childhood Hijaiyah Letter Recognition - Zakia Assidiki; Ali Formen; Diana Diana (Postgraduate, University of Mataram, 2026)
Hijaiyah letter recognition is a fundamental aspect of early Qur’anic literacy that requires developmentally appropriate teaching methods. However, early childhood education institutions still face challenges in selecting effective approaches to support children’s early reading skills. This study aimed to examine the effectiveness of the Al-Bayan method in improving Hijaiyah letter recognition among early childhood learners at TK Negeri Pembina Rantau, Aceh Tamiang Regency. The research employed a quantitative quasi-experimental design using a one-group pretest–posttest model. The sample consisted of 35 children selected through total sampling. Data were collected using Hijaiyah letter recognition tests and structured observation sheets. Data analysis included descriptive statistics, normality testing, paired sample t-test, and N-Gain analysis. The results showed a significant improvement in children’s Hijaiyah letter recognition after the implementation of the Al-Bayan method, with a mean difference of 26.30 and a significance value of p < 0.05. The N-Gain analysis indicated a moderate level of improvement, demonstrating the instructional effectiveness of the method. These findings suggest that the Al-Bayan method can be effectively implemented in early childhood Qur’anic learning to strengthen Hijaiyah letter recognition through structured repetition, guided practice, and child-centered instruction, providing practical guidance for educators in designing effective early Qur’anic literacy programs.